Mathematical competencies: a case study on semiotic systems and argumentation in an Italian High School. Issue 6 (3rd July 2021) - Capone, Roberto; Adesso, Maria Giuseppina; Del Regno, Flora; Lombardi, Laura; Tortoriello, Francesco Saverio
Abstract : This paper describes the main findings of a national action-research project, promoted by Regional School Office of Campania (South of Italy), aimed at improving numeracy and mathematical literacy through supporting schools' activities. The main focus is on processes underlying the creation of capabilities in representation, reasoning and communication. They have been investigated through creation of appropriate activities on the management of different semiotic systems and argumentation. About 400 fifteen-years- old students have been involved in the experimentation, divided into 20 high schools classes, in the Campania Region (South of Italy). The activities were designed to improve students' capabilities to solve real world problems, according to the OECD's Programme for International Student Assessment (PISA) framework. We investigated if the experimental activities might influence the acquisition of representation and communication skills and improve the PISA levels. We showed the project's rationale, its methodological choices, and theoretical framework. A protocols' analysis on conversion between various semiotic systems is also shown, mainly in two different schools' types (a Professional Institute and a Scientific High School). Finally, a quantitative analysis of the improvement of the PISA levels has been carried out, together with a discussion about the connection between the improvement of the mathematical skills and the realized activities.